Game Plan: a strategy for delivering Government`s sport and physical activity objectives (Eigenverlag, 2002)
1. Millions of people take part in sport and physical activity, both as a source of fun and to improve their health. Much of this happens without any involvement by government. However, government has a role to play in widening opportunities to participate, in developing talent, and in enabling our sportsmen and women to compete at the highest levels. The Strategy Unit`s role has been to review in detail where and how government can best add value. 2. We conclude that government should set itself two overarching objectives: • a major increase in participation in sport and physical activity, primarily because of the significant health benefits and to reduce the growing costs of inactivity; and • a sustainable improvement in success in international competition, particularly in the sports which matter most to the public, primarily because of the "feelgood factor" associated with winning. 3. In order to achieve this we make recommendations in four areas: • Grassroots participation: a wide range of initiatives are needed, with a focus on economically disadvantaged groups, in particular young people (the focus of much current policy), women and older people. These need to tackle all the barriers to participation (such as lack of time, cost, information or motivation), as well as failures in provision (poor coaches or facilities). • High Performance sport: there needs to be a better prioritisation of which sports are funded at the highest level; better development of talented sportsmen and women to help them reach that level; with funding streams and service delivery more focused on customer needs. • Mega sporting events: there should be a more cautious approach to hosting these events. A set process for government involvement, including a clear assessment of the benefits is needed. • Delivery: organisational reform and determining exactly what works is needed before the Government considers further increases to its investment in sport. Less money should go to bureaucrats and more to the end user. Public, private and voluntary sectors need to work together better towards a common goal. 4. The report addresses the following questions: • Where are we now? The facts about sport and physical activity in the UK today, and where problems lie (chapter 1). • Why do we care? The benefits sport and physical activity brings, and when government should intervene (chapter 2). • Where do we want to be? The vision for sport and physical activity in 2020 (chapter 3). • How are we going get there? Recommendations for participation, high performance sport, mega sporting events (chapters 4-6); and for delivering recommendations in all three of these areas (chapters 7-8).